The role and tasks of law enforcement authorities in the ‘external’ protection of the state (Academic Journal of Internal Affairs, 2022)
Aim: The aim of this study is to point out current differences in the field of different procedures of law enforcement agencies working at the border. Namely, how certain rules of border control and activities of other authorities working on the borders harmonise with the common EU border protection, policies and procedures. The paper aims to draw up a sketchy overview of these systems of two EU member states (Hungary and Germany) by highlighting the main differences and similarities.Methodology: The research is based primarily on the analization of written materials, documents and processing of relevant Hungarian and German legislation. In my access to German regulations I was assisted by a Baden-Württemberg police officer.Findings: My main hypotheses have been that the procedures of the Hungarian and German law enforcement agencies are different. At the same time, it should be clear that there are many similarities between the common federal and EU regulations. The problems detected and suggestions formulated during the research and as a part of the study are well detectable.Value: On the researched and processed topic emerge always changing new challenges and the mentioned law enforcement agencies require new procedural and regulatory techniques accordingly. Further research may be justified by multifaceted factors that challenge the mentioned law enforcement agencies, such as the security risks affecting the Member States of the European Union (illegal migration, neighboring war situations, etc.). The main task of the law enforcement agencies is to maintain and ensure public order and public safety. Order must also be protected from external danger. The work presents the German-Hungarian police activity performing the task of border protection, presenting common features and differences.
Keywords: border protection; public order; public security; Schengen standard